2017
DOI: 10.1080/19490976.2017.1339003
|View full text |Cite
|
Sign up to set email alerts
|

Loop ileostomy-mediated fecal stream diversion is associated with microbial dysbiosis

Abstract: Loop ileostomy is an effective procedure to protect downstream intestinal anastomoses. Ileostomy reversal surgery is often performed within 12 months of formation but is associated with substantial morbidity due to severe post-surgical complications. Distal ileum is deprived of enteral nutrition and rendered inactive, often becoming atrophied and fibrotic. This study aimed to investigate the microbial and morphological changes that occur in the defunctioned ileum following loop ileostomy-mediated fecal stream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 43 publications
3
81
2
2
Order By: Relevance
“…This study has shown that an ileostomy is associated with an increased risk of major LARS. While it was not possible to prove a causal relationship, it is plausible due to the potential impact of ileostomy on colonic inflammation, nutrition and atrophy . Information regarding functional outcome and quality of life therefore needs to be considered and conveyed to patients along with other factors influencing the risk/benefit ratio in stoma formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that an ileostomy is associated with an increased risk of major LARS. While it was not possible to prove a causal relationship, it is plausible due to the potential impact of ileostomy on colonic inflammation, nutrition and atrophy . Information regarding functional outcome and quality of life therefore needs to be considered and conveyed to patients along with other factors influencing the risk/benefit ratio in stoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, there is a paucity of literature from well‐designed clinical trials comparing functional and quality of life outcomes for patients with and without an ileostomy. If diversion of luminal content contributes to inflammation and atrophy, it is plausible that the duration of this disruption may play a role in the ultimate functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that reshaped gastrointestinal (GI) environments post-surgery affect microbiota in the GI tract, altering the composition of the microbiome [9,10]. Diversion colitis, also known as disuse colitis, is a well-known postoperative condition associated with dysbiosis and is described as an imbalance between potentially beneficial and pathogenic bacteria residing in the GI tract [11].…”
Section: Introductionmentioning
confidence: 99%
“…In patients who undergo delayed ileostomy closure, it is possible that preoperative stimulation of the defunctioned colon may be beneficial. The rationale for this is that it may reverse the microbial dysbiosis and villous atrophy observed in defunctioned bowel , as these factors impair absorptive capacity . Alteration in the microbiome of diverted bowel has been well‐studied with Clostridium difficile infection, a recognized complication of ileostomy closure .…”
Section: Introductionmentioning
confidence: 99%